Arrested development of Cooperia and Haemonchus in weaned zebu calves reared extensively in a tropical environment - Melo, Hermano J.H. de; Gomes, Alberto (Pesquisa Agropecuaria Brasileira, 2014)
Changes in the adult and immature gastrointestinal nematode populations of ten weaned Zebu calves, eight months old, were studied. The following nematode species were recovered from necropsy: Haemonchus contortus, H. similis, Trichostrongylus axei, Cooperia pectinata, C. punctata, Bunostomum phlebotomum, Trichuris discolor and Oesophagostomum radiatum. The most prevalent genera found were Cooperia spp. and Haemonchus spp. and studies on arrested development were concerned with these genera. The results obtained in this experiment support the idea that arrested development of Cooperia spp. and Haemonchus spp. does occur in this region during the dry winter period, although the number of arrested forms recovered here was not so spectacular as that by other workers in temperate and cool climates.